COVID-19 infection and vaccination uptake in men and gender-diverse people who have sex with men in the UK: analyses of a large, online community cross-sectional survey (RiiSH-COVID) undertaken November-December 2021 - Dana Ogaz; Hester Allen; David Reid; Jack R. G. Brown; Alison R. Howarth; Caisey V. Pulford; Catherine H. Mercer; John Saunders; Gwenda Hughes; Hamish Mohammed (BMC, 2023)
Abstract Background Men and gender-diverse people who have sex with men are disproportionately affected by health conditions associated with increased risk of severe illness due to COVID-19 infection. Methods An online cross-sectional survey of men and gender-diverse people who have sex with men in the UK recruited via social networking and dating applications from 22 November-12 December 2021. Eligible participants included self-identifying men, transgender women, or gender-diverse individuals assigned male at birth (AMAB), aged ≥ 16, who were UK residents, and self-reported having had sex with an individual AMAB in the last year. We calculated self-reported COVID-19 test-positivity, proportion reporting long COVID, and COVID-19 vaccination uptake anytime from pandemic start to survey completion (November/December 2021). Logistic regression was used to assess sociodemographic, clinical, and behavioural characteristics associated with SARS-CoV-2 (COVID-19) test positivity and complete vaccination (≥ 2 vaccine doses). Results Among 1,039 participants (88.1% white, median age 41 years [interquartile range: 31-51]), 18.6% (95% CI: 16.3%-21.1%) reported COVID-19 test positivity, 8.3% (95% CI: 6.7%-10.1%) long COVID, and 94.5% (95% CI: 93.3%-96.1%) complete COVID-19 vaccination through late 2021. In multivariable models, COVID-19 test positivity was associated with UK country of residence (aOR: 2.22 [95% CI: 1.26-3.92], England vs outside England) and employment (aOR: 1.55 [95% CI: 1.01-2.38], current employment vs not employed). Complete COVID-19 vaccination was associated with age (aOR: 1.04 [95% CI: 1.01-1.06], per increasing year), gender (aOR: 0.26 [95% CI: 0.09-0.72], gender minority vs cisgender), education (aOR: 2.11 [95% CI: 1.12-3.98], degree-level or higher vs below degree-level), employment (aOR: 2.07 [95% CI: 1.08-3.94], current employment vs not employed), relationship status (aOR: 0.50 [95% CI: 0.25-1.00], single vs in a relationship), COVID-19 infection history (aOR: 0.47 [95% CI: 0.25-0.88], test positivity or self-perceived infection vs no history), known HPV vaccination (aOR: 3.32 [95% CI: 1.43-7.75]), and low self-worth (aOR: 0.29 [95% CI: 0.15-0.54]). Conclusions In this community sample, COVID-19 vaccine uptake was high overall, though lower among younger age-groups, gender minorities, and those with poorer well-being. Efforts are needed to limit COVID-19 related exacerbation of health inequalities in groups who already experience a greater burden of poor health relative to other men who have sex with men.